2002
DOI: 10.1002/cncr.10629
|View full text |Cite
|
Sign up to set email alerts
|

The novel and effective nonplatinum, nontaxane combination of gemcitabine and vinorelbine in advanced nonsmall cell lung carcinoma

Abstract: BACKGROUNDGemcitabine and vinorelbine are two of the most active third‐generation agents for the treatment of advanced nonsmall cell lung carcinoma (NSCLC). The authors conducted a formal Phase II trial to evaluate the efficacy of this combination in both untreated and previously treated patients with Stage IIIB (with pleural effusion) or Stage IV NSCLC.METHODSA total of 78 patients were treated on the current Phase II trial of front‐line or second/third‐line therapy with gemcitabine and vinorelbine in NSCLC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…The combination of gemcitabine and vinorelbine has been investigated in previously treated and untreated patients with stage IIIb and IV disease (40). In the untreated group, 16 of 42 patients (36%) experienced a partial response, median overall survival was 10.1 months, and 1-and 2-year survival was 42.9% and 31.6%.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of gemcitabine and vinorelbine has been investigated in previously treated and untreated patients with stage IIIb and IV disease (40). In the untreated group, 16 of 42 patients (36%) experienced a partial response, median overall survival was 10.1 months, and 1-and 2-year survival was 42.9% and 31.6%.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports of a salvage GV regimen in relatively younger patients (median age at each study 55-66 years) [15,16,17,21,22]. Most of these studies reported a favorable response rate (17.0-31.3%) and prolonged OS (6.5-8.5 months) [15,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies reported a favorable response rate (17.0-31.3%) and prolonged OS (6.5-8.5 months) [15,16,17]. However, some studies which used a lower dose (gemcitabine 800 mg/m 2 ) than that of our study (1,000 mg/m 2 ) [22] and a biweekly schedule [21] as salvage therapy showed a disappointing response rate of 0-6.25%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 DOC is considered to be one of the most important anticancer drugs for clinical use. It acts by inhibiting the microtubular network that is essential for mitotic and interphase cellular functions.…”
Section: Introductionmentioning
confidence: 99%